Underexpression of peroxisome proliferator-activated receptor (PPAR)γ in PAX8/PPARγ-negative thyroid tumours - Marques, A. R. (2022)
Funding: We gratefully acknowledge the technical assistance of Ms Teresa Pereira. Ana Rita Marques is a recipient of a PhD fellowship (PRAXIS XXI/BD/21329/99) from Fundação para a Ciência e Tecnologia. This work was supported by Núcleo Regional do Sul Liga Portuguesa Contra O Cancro (Terry Fox) and Fundação para a Ciência e Tecnologia (POCTI/CBO/48922/2002), Portugal.